Linguistic Validation and Cross-Cultural Adaptation of the Liverpool Osteoarthritis in Dogs Instrument for the German- and Spanish-Speaking Populations - Radke, Heidi; Reyes Rodriguez, Natalia Andrea; Lafuente, Pilar; Cianciolo, Chiara; Cella, Paul; Joeris, Alexander (Vet Comp Orthop Traumatol, 2026)
Background The Liverpool Osteoarthritis in Dogs (LOAD) is a widely used observer- reported outcome measure questionnaire for assessing pain in dogs with osteoarthri- tis. This study aimed to linguistically validate and culturally adapt the LOAD for German- and Spanish-speaking populations. Methods The process followed the Functional Assessment of Chronic Illness Therapy translation methodology and involved two forward translations, a reconciliation of the forward translation, back translations, expert reviews, and cognitive debriefing inter- views with a representative sample of dog carers. A universal approach was adopted to generate Universal German and Universal Spanish versions of the LOAD suitable for use in all German- and Spanish-speaking countries. Results The two forward translations and the reconciliation phase showed 12 and 6 discrepancies for the German and Spanish LOAD, respectively. Comparing the back- ward translation with the original version identified 13 items or instructions in the German LOAD and 20 in the Spanish LOAD that required retranslation. The review panel resolved both conceptual and literal discrepancies, while input from cognitive inter- view participants contributed to 6 additional revisions for the Universal German version and 15 for the Universal Spanish versions of the LOAD. Conclusion This stepwise approach resulted in linguistically validated and culturally adapted universal versions of the LOAD for the German- and Spanish-speaking populations.
Keywords: observer-reported outcome measures; translation; linguistic validation; canine; orthopaedic